2020
DOI: 10.1016/j.jeurceramsoc.2020.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical assessment of grain boundary energies in polycrystalline uranium dioxide

Abstract: Uranium dioxide ceramics are widely used as nuclear fuels. Thus, it is important to understand the role of the grain boundaries (GBs) which decisively govern the properties of these polycrystalline materials and subsequently determine their performances. Here, we report a coupled numerical-experimental approach enabling to assess GB energies. Firstly, GB formation energies (γgb) were computed for 34 symmetric tilt GBs in UO2 with molecular dynamics simulations at 1700 K. The surface energies (γS) relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…We showed that the cleavage energy seems to decrease with the misorientation angle of CSL grain boundaries 19 . Using the thermal grooving method, we have also measured the formation energies of several CSL grain boundaries on a polycrystalline sample 8 . Measured energies appear to be in good agreement with calculated energies, which demonstrates the reliability of the calculations and the relevance of our coupled approach.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…We showed that the cleavage energy seems to decrease with the misorientation angle of CSL grain boundaries 19 . Using the thermal grooving method, we have also measured the formation energies of several CSL grain boundaries on a polycrystalline sample 8 . Measured energies appear to be in good agreement with calculated energies, which demonstrates the reliability of the calculations and the relevance of our coupled approach.…”
Section: Introductionsupporting
confidence: 59%
“…In a previous work, we simulated the most common grain boundaries observed in the UO 2 polycrystalline materials using four empirical potentials. As a result of this study, the CRG potential was selected to assess the grain boundary energy mainly for two reasons: The energies calculated using this potential at 300 K were consistent with the classification of the grain boundaries as a function of the linear fraction measured by EBSD 19 and in good agreement with measured energies for various grain boundaries 8 ; This potential yielded good results with regard to the evolution of thermodynamic properties with temperature (see Ref. [30] and references therein). …”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations